Studies Literature: Connection Style Life with Incident Breast Cancer - Marvina, Ria Ayu (Jurnal Kesehatan Metro Sai Wawai, 2024)
Introduction: Breast cancer is one of the non-communicable diseases that tends to continue to increase every year, so it can be said that the burden that the world has to bear due to the disease is increasing. Based on Globocan data in 2018 in Indonesia, breast cancer is in first place with the number of 16.7% cases, with the number of deaths as high as 11.0% matter This cannot be separated from the factors that trigger breast cancer, one of which is lifestyle. Objective: This literature review aims to determine the relationship between lifestyle, namely diet, physical activity, and exposure to cigarette smoke, with breast cancer. Methods: This study uses a literature review design. This study consists of 5 articles (3 national and 2 international) from 2005-2017. Data collection using literature studies obtained from Google Scholar and PubMed. From the research obtained, 3 literatures discuss cigarette smoke exposure variables, 3 literatures discuss smoking pattern variables, and 3 literatures discuss 3 variables of activity physique. Results: Data analysis was carried out by looking at the research year starting from the most recent and then stepping back to Which most long. From the literature obtained, 3 studies showed that there was a relationship between exposure to cigarette smoke and the incidence of breast cancer, 3 studies showed that there was a relationship between diet and the incidence of breast cancer, and 3 studies showed that there was a relationship between physical activity and incidence of breast cancer. Conclusion: There is a relationship between exposure to cigarette smoke, poor diet, and lack of physical activity with the incidence of breast cancer in women.